A spatial analysis of EPCs in The Belfast Metropolitan Area housing market. Issue 1 (2nd January 2020) - McCord, Michael; Lo, Daniel; Davis, Peadar Thomas; Hemphill, Lesley; McCord, John; Haran, Martin
ABSTRACT: Energy performance remains a debated topic in real estate, particularly with reference to the capitalisation effect with property value. An emerging corpus of research studies have investigated the relationship between energy performance characteristics and the role of Energy Performance Certificates. Whilst these studies have consistently demonstrated that a pricing effect exists, some recent studies have shown that Energy Performance Certificates (EPCs) are more complex and inconclusive, particularly when accounting for data limitations and changing model specifications. Moreover, a majority of these studies neglect to adequately account for absolute location and therefore, arguably, do not examine the geographic variation between EPCs and property value across the housing market setting. This study presents one of the first spatial analyses of EPCs using transactions for the Belfast Metropolitan Area. In evaluating whether spatial effects exist between EPCs and house prices, a number of spatial tests are performed and a series of models are developed to account for spatial dependency and determine whether there are any spatially correlating effects. The findings indicate that EPCs comprise a partial effect on house prices, and importantly, there are pricing differentials in the spatial variation in EPCs with the pricing effects conforming to both spatial clustering and randomness.